Clinical profile of infectious causes of thrombocytopenia in children admitted in tertiary care hospital in Eastern Uttar Pradesh: a prospective study - Singh, Kushagra; Aggarwal, Priyanka; Gupta, Vineeta; Srivastava, Chandradeep; Sidar, Minketan (International Journal of Contemporary Pediatrics, 2025)
Background: Thrombocytopenia, a common hematological abnormality in pediatric patients, can result from diverse infectious and non-infectious causes. Identifying the clinical and etiological profile of thrombocytopenia is crucial for early diagnosis and effective management. To assess the clinical, laboratory and etiological characteristics of thrombocytopenia due to infectious etiology in hospitalized pediatric patients and evaluate their outcomes. Methods: This prospective observational study was conducted in the Department of Pediatrics, Institute of Medical Sciences, Banaras Hindu University, Varanasi, from August 2023 to July 2024. Pediatric patients aged 1–16 years with thrombocytopenia due to infectious causes were included. Demographic details, clinical features, laboratory parameters, complications and outcomes were recorded. Results: Among 125 children, majority were 1–5 years old (37.6%), with a slight male predominance (53.6%). Fever was the most common presentation (100%), followed by bleeding manifestations (25.6%). Dengue (34.4%) and Scrub Typhus (21.6%) were the leading etiologies. Severe thrombocytopenia (<10,000/ul) was significantly associated with increased PICU admissions (p=0.0052) and mechanical ventilation (p=0.0001). The mortality rate was 16.8%. Significant predictors of adverse outcomes were ARDS (p=0.0274), vasopressor requirement (p=0.0002) and coagulation abnormalities (p=0.0000). Conclusions: Infectious diseases, particularly vector-borne illnesses such as dengue and scrub typhus, are predominant causes of thrombocytopenia in pediatric patients. Severe thrombocytopenia correlates with higher PICU admissions and mortality, emphasizing the need for early identification and targeted management strategies.